Global value chains and deep preferential trade agreements: promoting trade at the cost of domestic policy autonomy? - Dominique Bruhn (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
This paper evaluates the role of preferential trade agreements (PTAs) in the context of global value chains. Given the interconnectedness of trade and investment, preferential trade agreements not only contribute to participation and value capture by eliminating traditional trade barriers, they also provide a framework for economic governance regulating behind-the-border policies. While this is an important device for ensuring commitment to creating a reliable business environment, deep trade agreements also tend to restrict policy autonomy. Governing global value chains by means of deep trade agreements is thus a double-edged sword. Against this background, developing countries should carefully assess the pros and cons associated with PTA membership. In order to successfully reap the benefits, PTAs should be geared towards developing country needs by maintaining the flexibility necessary for developmental purposes. This will require negotiation skills on the part of developing countries as well as technical assistance for implementation on the part of developed countries. Moreover, given the increasingly global character of value chains, both developed and developing countries should pursue negotiations at the multilateral level in order to make optimal use of the opportunities created by global value chain trade. By looking at deep PTAs, this paper combines the literature on regional integration with the new strand of global value chain research – without neglecting the traditional view on global value chains and development which stresses the role for complementary policies. The paper concludes by translating the findings into policy recommendations and pointing out gaps in the literature that should be addressed to better inform policy-makers.
Keywords: 330; Handel und Investitionen